2016
DOI: 10.1245/s10434-016-5277-1
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms for Predicting Axillary Response to Neoadjuvant Chemotherapy in Clinically Node-Positive Patients with Breast Cancer

Abstract: Nomograms incorporating routine clinicopathologic parameters can predict axillary pCR in node-positive patients receiving NAC and may help to inform treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
47
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 30 publications
7
47
1
Order By: Relevance
“…Therefore, additional tools may prove helpful in estimating axillary nodal response to NAC in patients with clinical node-positive breast cancer, and in identifying which patients who do not require ALND. Models have been designed to predict the probabilities or risks of clinical outcomes, thereby assisting clinicians and patients in determining how to manage breast cancer [ 14 15 ]. These models have limitations, however, because they did not evaluate tumor response after NAC, but because they were not validated using data from an institution not involved in model development.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, additional tools may prove helpful in estimating axillary nodal response to NAC in patients with clinical node-positive breast cancer, and in identifying which patients who do not require ALND. Models have been designed to predict the probabilities or risks of clinical outcomes, thereby assisting clinicians and patients in determining how to manage breast cancer [ 14 15 ]. These models have limitations, however, because they did not evaluate tumor response after NAC, but because they were not validated using data from an institution not involved in model development.…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with previous research given that high-grade tumors are associated with higher rates of axillary pCR. [30][31][32][33] The increasing use of NST and the inability to predict the axillary lymph node status after NST have raised questions regarding the patients who do need PMRT and increased the complexity of immediate breast reconstruction planning. Immediate breast reconstruction reduces the number of surgical procedures and has a better aesthetic outcome due to decreased scarring and preservation of the breast skin envelope.…”
Section: Discussionmentioning
confidence: 99%
“…These observations are consistent with previous studies regarding variable sensitivity to chemotherapy, according to tumor grade and subtype . A recent study also revealed that nodal complete response was more likely to be achieved in tumors with high nuclear grade, HER2‐positive tumors, and HR‐negative tumors . HR‐positive breast cancer is known to be less sensitive to NAC, compared with HER2‐positive and triple‐negative breast cancers …”
Section: Discussionmentioning
confidence: 99%
“…Neo‐adjuvant chemotherapy (NAC) is increasingly being used in patients with node‐positive disease . Notably, 40%‐50% of patients convert from node‐positive to node‐negative disease following NAC . The ACOSOG Z1071 and National Surgical Adjuvant Breast and Bowel Project (NSABP) B‐27 trials collectively demonstrated that SLNB, rather than ALND, is applicable for surgical management following NAC .…”
Section: Introductionmentioning
confidence: 99%